New thermal study of polymerization and degradation kinetics of methylene diphenyl diisocyanate - da Silva, José Eduardo Estevam [UNESP]; Alarcon, Rafael Turra [UNESP]; Gaglieri, Caroline [UNESP]; Magdalena, Aroldo Geraldo [UNESP]; da Silva-Filho, Luiz Carlos [UNESP]; Bannach, Gilbert [UNESP] (My University, 2018)
This work investigates the thermal polymerization process of a methylene diphenyl diisocyanate (MDI) monomer as well as its thermal degradation following the ICTAC recommendations. MDI monomer is widely used as a synthetic resin in the production of MDF panels, as it provides compaction of the eucalyptus fibers by polymerization. Thermogravimetry/derivative thermogravimetric-differential thermal analysis (TG/DTG-DTA), differential scanning calorimetry, and mid-infrared spectroscopy were used in this study. The polymerization process (An) and degradation (Fn) process exhibited activation energy equal to 149.70 and 80.22 kJ mol−1, respectively. The combined the FTIR and kinetic information makes it possible to suggest the mechanism reaction, which is an inedited data in literature.
Keywords: Degradation; Methylene diphenyl diisocyanate; Non-isothermal kinetics; Polymerization; Thermal studies